STRATEGIES FOR DEVELOPING SUSTAINABLE AND COMPETITIVE CLUSTER FOR SHRIMP INDUSTRY - Fauzi, Anas M.; Indrawan, R.Dikky; Setiawan Slamet, Alim; Ratna Dewi, Farida; Kartika, Lindawati; S, Firmansjah (School of Business, Bogor Agricultural University (SB-IPB), 2012)
Kampung Vannamei as shrimp cluster is being developed since 2004 by PT CP Prima, tbk Surabaya through Shrimp Culture Health Management transformation technology to several traditional farmers in Gresik, Lamongan, Tuban, and Madura areas. The research objectives aims to identify and mapping of stakeholder, to analyze interaction of stakeholders, to formulate strategy from internal and external environment factors and to set priority on strategy to develop sustainable and competitive shrimp cluster in the Kampung vannamei. Primary data was collected through stakeholders’ discussion forums, questionnaires, and interviews with relevant actors. Observations to the business unit also performed to determine the production and business conditions, particularly in capturing information about the threat and challenges. While the secondary data is used in policy documents national and local area statistics, and relevant literature. Analyses were performed by using the SRI International cluster pyramid, diamond porter’s analysis, SWOT and Matrix TOWS analysis, and analytical hierarchy process. Analyses were performed by the methods discussed in qualitative and descriptive. There are 7 strategies could be implemented to develop sustainable and competitive shrimp cluster. However, it is recommended to implement the strategy base on priority, which the first priority is strategy to improve linkages between businesses in the upstream and downstream industries into multi stakeholders’ platform in shrimp industry.Keywords: Shrimp, Cluster, Competitiveness, Diamond Porter, SWOT Analysis, AHP